Quantifying Polaron Mole Fractions and Interpreting Spectral Changes in Molecularly Doped Conjugated Polymers. (28th December 2021) - Moulé, Adam J.; Gonel, Goktug; Murrey, Tucker L.; Ghosh, Raja; Saska, Jan; Shevchenko, Nikolay E.; Denti, Ilaria; Fergerson, Alice S.; Talbot, Rachel M.; Yacoub, Nichole L.; Mascal, Mark; Salleo, Alberto; et al.
Abstract: Molecular doping of conjugated polymers causes bleaching of the neutral absorbance and results in new polaron absorbance transitions in the mid and near infrared. Here, the concentration dependent changes in the spectra for a series of molecularly doped diketopyrrolopyrrole (DPP) co‐polymers with a series of ultra‐high electron affinity cyanotrimethylenecyclopropane‐based dopants is analyzed. With these strong dopants the polaron mole fraction (Θ) reaches saturation. Analysis of the full spectrum enables separation of neutral and polaron signals and quantification of the polaron mole fraction using a simple noninteracting site model. The peak ratios for both neutral and polaron peaks change systematically with increasing polaron mole fraction for all measured polymers. Analysis of the spectral changes indicates that the polaron mole fraction can be quantified to within 5%. While the total change in the absorbance spectrum with increasing polaron mole fraction is linear, the lowest energy polaron peak (P1) grows nonlinearly, which indicates increased polarization/delocalization. Molecular doping of polymers that form either H‐ or J‐aggregates shows systematically different spectral changes in the vibronic peak ratios of the neutral spectra and provides insights into the polymer configuration at undoped sites in the film. Abstract : Molecular dopants charge transfer with semiconducting polymers, resulting in excited polymer states (polarons) and dopant counterions. This process produces an observable bleach in the optical absorbance of the intrinsic polymer and a simultaneous growth of optical polaron transitions. Quantifying these changes enables estimation of the polaron mole fraction and analysis of optoelectronic coupling as a function of the doping level.